If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -4(1 + 5X) + -7(-5 + 8X) = 31 (1 * -4 + 5X * -4) + -7(-5 + 8X) = 31 (-4 + -20X) + -7(-5 + 8X) = 31 -4 + -20X + (-5 * -7 + 8X * -7) = 31 -4 + -20X + (35 + -56X) = 31 Reorder the terms: -4 + 35 + -20X + -56X = 31 Combine like terms: -4 + 35 = 31 31 + -20X + -56X = 31 Combine like terms: -20X + -56X = -76X 31 + -76X = 31 Add '-31' to each side of the equation. 31 + -31 + -76X = 31 + -31 Combine like terms: 31 + -31 = 0 0 + -76X = 31 + -31 -76X = 31 + -31 Combine like terms: 31 + -31 = 0 -76X = 0 Solving -76X = 0 Solving for variable 'X'. Move all terms containing X to the left, all other terms to the right. Divide each side by '-76'. X = 0 Simplifying X = 0
| 3(x-5)-14=2(x-7)+2 | | 2(s-3)=15 | | x-3+2=0 | | -5(m+10)=100 | | 4(x+7)=36 | | 30=-2(1+2N)+8(N+8) | | -2x-1=7+2x | | 4(3x+15)=0 | | -3s+(-4)=25 | | -7(-5V+1)+5(8+7V)=33 | | 3s+4=25 | | 2(3x-7)=3x-5 | | X+(-4)=8 | | 2x*x^2-16*4x+3=0 | | 5(6+8B)+8(B-5)=-10 | | m-4m+12=3 | | 5x+10=9x+15 | | [(x-2)-5][(x-2)+3]=0 | | 18+2x=-54 | | 17x+64=13 | | -256=8(7X-6)-4X | | 24x+7*8= | | 5a-2+b-3b+2a= | | 5x-3x+40=50 | | x+109=1+89 | | 3x^2-8x-19=0 | | 70=-17.5n | | 2x=3x-10 | | 12v-3(2+4v)+6= | | 6(1-6X)-4(3X+6)=30 | | -15x+7x+1=3-8 | | 3x^2-22x=0 |